Improving Students’ Motivation in Reading Skill through Illustrated Text at SMA Gajah Mada 3 Palembang - Agustiawati, Hartini (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2023)
The Purpose of the study is to determine the use of Illustrated text to improve students’ motivation in Reading Skill at SMA Gajah Mada Palembang. Quasi experimental was used. An illustrated text has been given to the students at SMA Gajah Mada Palembang. There were some questions related to the text. The result showed that there was good result for students who taught by Illustrated text. Based on the research, Illustrated text can be used to improve students’ motivation in Reading skill. This method can be sollution to help students’ to learn and it is reccommended for the next researchers and teachers who has interest to conduct reading skill as their research